Detection of Cerebrovascular Loss in the Normal Aging C57BL/6 Mouse Brain Using in vivo Contrast-Enhanced Magnetic Resonance Angiography - Hill, Lindsay K.; Hoang, Dung Minh; Chiriboga, Luis A.; Wisniewski, Thomas; Sadowski, Martin J.; Wadghiri, Youssef Z. (Frontiers in Aging Neuroscience, 2020)
Microvascular rarefaction, or the decrease in vascular density, has been described in the cerebrovasculature of aging humans, rats and, more recently, mice in the presence and absence of age-dependent diseases. Given the wide use of mice in modeling age-dependent human diseases of the cerebrovasculature, visualization and quantification of the global murine cerebrovasculature is necessary in establishing the baseline changes that occur with aging. In order to provide in vivo whole brain imaging of the cerebrovasculature in aging C57BL/6 mice longitudinally, contrast-enhanced magnetic resonance angiography (CE-MRA) was employed using a house-made gadolinium-bearing micellar blood pool agent. Enhancement in the vascular space permitted quantification of the detectable, or apparent, cerebral blood volume (aCBV), which was analyzed over 2 years of aging and compared to histological analysis of the cerebrovascular density. A significant loss in the aCBV was detected by CE-MRA over the aging period. Histological analysis via vessel-probing immunohistochemistry confirmed a significant loss in the cerebrovascular density over the same 2-year aging period, validating the CE-MRA findings. While these techniques use widely different methods of assessment and spatial resolutions, their similarity in detected vascular loss corroborates the growing body of literature describing vascular rarefaction in aging and suggests that such age-dependent changes can contribute to cerebrovascular and neurodegenerative diseases, which are modeled using wild-type and transgenic laboratory rodents.